Incentives for Innovation in Pollution Control: Emission Standards Revisited - Peter Michaelis; Jürgen Dietz (Universität Augsburg, Institut für Volkswirtschaftslehre, 2004)
Conventional analysis of the economics of environmental policy usually claims that emission taxes induce a stronger incentive for an improvement in pollution abatement technologies compared to emission standards. In contrast, recent empirical studies reveal that there is no systematic relationship between improvements in pollution abatement technologies and the policy instrument chosen. The present paper tries to clarify this contradiction. In the first step the paper shows that the conventional model of innovation in pollution control under different policy regimes is deficient in at least two ways: It neglects policy impacts on the firms? output level and it assumes a rather unrealistic type of emission standard. In the second step the paper presents a more elaborated model which tries to overcome these shortcomings. Using this model it is shown that the impact on innovation in pollution control caused by taxes and standards strongly depends on the scale of technical progress as well as on the cost structure of the firm under consideration such that there is no unique ranking of the two policies. Finally, the paper discusses the policy implications of these findings.
urn:nbn:de:bvb:384-opus4-537637
Keywords: H23; Q55; 330; Emission Standards; Emission Taxes; Incentives to Innovate; Umweltauflage; Ökosteuer; Umweltabgabe; Umwelttechnik; Innovation; Ökonomischer Anreiz; Theorie